Development of a new categorization system for pesticides exposure to support harmonized reporting between EU Member States. (May 2016) - Settimi, Laura; Orford, Rob; Davanzo, Franca; Hague, Charlotte; Desel, Herbert; Pelclova, Daniela; Dragelyte, Gabija; Mathieu-Nolf, Monique; Adams, Richard; Duarte-Davidson, Raquel
Abstract: Objectives: European legislation requires reporting from Member States on acute poisoning incidents involving pesticides. However, standard rules for data collection and reporting have not yet been set out. The new categorization system presented in this paper is aimed at enabling Member States to gather comparable data and provide standard reporting on pesticide poisoning exposures. Materials and methods: European Regulations providing separate official categorization of biocidal and plant protection pesticides, were used as a basis to build up a unified pesticide categorization and coding system. Data on selected pesticide exposures collected by Poison Control Centres in six EU countries were reviewed, categorized and reported according to the proposed system. Results: The resulting pesticide categorization system has two dimensions. The first part identifies the main category of use, i.e. biocide/plant protection pesticide/unknown, and the secondary category of use, e.g. Rodenticides, Insecticides and acaricides . The second part of the system is organized into two levels: level one identifies chemical grouping, e.g. Coumarins, Pyrethrins / pyrethroids, while level two identifies the active compound by using its Chemical Abstract Service Registry Number. The system was used to provide a unified categorization to compare exposures to plant protection and biocidal Rodenticides and Pyrethrins / pyrethroids Insecticides and acaricides identified by six EU member states. Conclusion: The developed pesticide categorization system was successfully applied to data extracted from different databases and was able to make the required information comparable. The data reported filling in common templates containing a pre-ordinate list of active compounds categorized according the proposed system, highlighted different capabilities in data collection and recording, showing that some of the collaborating centres were not able to distinguish between main categories of pesticide products or provide information on active compounds. The results indicate that a special effort should be dedicated to support detailed data recording at national level. Providing common tools to systematically report to the EU Commission hazardous exposures to pesticides, as well as to other selected categories of products, could allow for data comparability between Member States and greatly improve post marketing surveillance and alerting systems in Europe. Highlights: New pesticide categorization system to provide standard reporting on poisoning and exposures Pesticide exposures data from six EU countries were reviewed, categorized and reported. System could greatly improve post marketing surveillance and alerting of pesticide exposures in Europe.